Determinants of fintech firms’ survivability-moderating role of fintech experience / Siti Nur Shuhada Nazuri - Nazuri, Siti Nur Shuhada (2023)
Financial technology (Fintech) has become a significant area of research because it is changing the economy and consumers' lives in unexpected ways. Fintech refers to companies or agents that use advanced and innovative technologies to connect them with financial services. Most researchers have studied the concept of Fintech, the development of Fintech, the relationship between Fintech and banks, and the impact of Fintech on the banking sector. The Fintech industry is characterized by intense competition and a high rate of company failures. Further understanding of the issues and contributing factors towards survivability of Fintech firms should be gathered and empirically tested. This research seeks to empirically investigate these issues, focusing on industry specific characteristics, firm specific characteristics, Fintech specific characteristics, and the experiences of Fintech firms in Malaysia, aiming to provide empirical evidence and insights into what contributes to the survivability of Fintech firms in the Malaysian context. Industry specific characteristics were represented by the independent variables of pressure intensity and regulatory support. Firm specific characteristics included the independent variables: firm size, size of the management team, and internationalization scope. Fintech capabilities represented Fintech specific characteristics. Additionally, Fintech experience acted as a moderator between firm specific characteristics and Fintech firms' survivability. In this study, a quantitative approach using the questionnaire survey method was used to collect data.